2014
DOI: 10.1038/srep05589
|View full text |Cite
|
Sign up to set email alerts
|

Environmental variability and biodiversity of megabenthos on the Hebrides Terrace Seamount (Northeast Atlantic)

Abstract: We present the first remotely operated vehicle investigation of megabenthic communities (1004–1695 m water depth) on the Hebrides Terrace Seamount (Northeast Atlantic). Conductivity-temperature-depth casts showed rapid light attenuation below the summit and an oceanographic regime on the flanks consistent with an internal tide, and high short-term variability in water temperature, salinity, light attenuation, aragonite and oxygen down to 1500 m deep. Minor changes in species composition (3–14%) were explained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 50 publications
(80 reference statements)
3
35
0
Order By: Relevance
“…However, the extent of damage to corals caused by bottom trawling is not quantified, although qualitative estimates indicate that such damage can be extensive, in particular in localized areas around fishing hotspots, such as the seamounts where corals are predominantly found (Althaus et al, 2009;Clark & Rowden, 2009;Parker et al, 2009). Other factors, including environmental factors such as depth-dependent water temperature, pH, calcite and aragonite saturation concentrations, are also likely to contribute both historically and contemporaneously (Henry et al, 2014;Miller, Rowden, Williams, & Häussermann, 2011;Tracey et al, 2013), but are thought to be of lesser importance than fishing pressure in modern times. However, the most recent study of possible impacts of fishing activity on deep-sea corals (Miller & Gunasekera, 2017) reported that genetic diversity of S. variabilis and the solitary cup coral Desmophyllum dianthus on fished and unfished seamounts was similar.…”
Section: Effective Population Sizesmentioning
confidence: 99%
“…However, the extent of damage to corals caused by bottom trawling is not quantified, although qualitative estimates indicate that such damage can be extensive, in particular in localized areas around fishing hotspots, such as the seamounts where corals are predominantly found (Althaus et al, 2009;Clark & Rowden, 2009;Parker et al, 2009). Other factors, including environmental factors such as depth-dependent water temperature, pH, calcite and aragonite saturation concentrations, are also likely to contribute both historically and contemporaneously (Henry et al, 2014;Miller, Rowden, Williams, & Häussermann, 2011;Tracey et al, 2013), but are thought to be of lesser importance than fishing pressure in modern times. However, the most recent study of possible impacts of fishing activity on deep-sea corals (Miller & Gunasekera, 2017) reported that genetic diversity of S. variabilis and the solitary cup coral Desmophyllum dianthus on fished and unfished seamounts was similar.…”
Section: Effective Population Sizesmentioning
confidence: 99%
“…Studies have highlighted the ability of live cold-water corals to maintain calcification at reduced pH (Maier et al, 2009; Form and Riebesell 2012) but synergistic effects with increasing temperature and longer-term effects on resource allocation and reproduction remain unknown. It is becoming clear that deep-water ecosystems may experience more natural variability in carbonate chemistry than was previously supposed (Findlay et al, 2013;Findlay et al, 2014) and that calcareous species can persist even in under-saturated conditions on Tasmanian seamounts (Thresher et al, 2011). However, undersaturated waters will be corrosive to dead coral skeletons that provide structural habitat for many other species, a factor potentially explaining the limited scleractinian coral reef framework on the Hebrides Terrace Seamount (Henry et al, 2014).…”
Section: Climate Change Including Acidification and Deoxygenationmentioning
confidence: 99%
“…It is becoming clear that deep-water ecosystems may experience more natural variability in carbonate chemistry than was previously supposed (Findlay et al, 2013;Findlay et al, 2014) and that calcareous species can persist even in under-saturated conditions on Tasmanian seamounts (Thresher et al, 2011). However, undersaturated waters will be corrosive to dead coral skeletons that provide structural habitat for many other species, a factor potentially explaining the limited scleractinian coral reef framework on the Hebrides Terrace Seamount (Henry et al, 2014). Increased carbon dioxide and reduced pH may also directly affect marine organisms' physiology, growth, and behaviour (Wicks and Roberts, 2012).…”
Section: Climate Change Including Acidification and Deoxygenationmentioning
confidence: 99%
“…There is evidence that seamounts form hot spots of biological activity in the oceans (Lavelle & Mohn, 2010;Morato et al, 2010). Analysis done by Rogers (1994) indicates that higher species richness detected at seamounts compared to coastal or oceanic areas can be a consequence of enhanced oceanic dynamical activity in these areas (Henry et al, 2014).…”
Section: Introductionmentioning
confidence: 99%